Status and trends of Arctic Ocean environmental change and its impacts on marine biogeochemistry: Findings from the ArCS project - Kikuchi, Takashi; Nishino, Shigeto; Fujiwara, Amane; Onodera, Jonaotaro; Yamamoto-Kawai, Michiyo; Mizobata, Kohei; Fukamachi, Yasushi; Watanabe, Eiji (Polar Science, 2021)
Ocean observation research theme under ArCS project, “Theme 4: Observational research on Arctic Ocean environmental changes”, aimed to elucidate the status and trends of ongoing Arctic Ocean environmental changes and to evaluate their impacts on Arctic marine ecosystem and the global climate system. For these purposes, we conducted field observations, mooring observations, laboratory experiments, numerical modeling, and international collaborative research focusing on the Pacific Arctic Region (PAR) and from Pan-Arctic point of views. As a result, we have published several scientific studies on environmental changes and their impact on the climate and ecosystem. In this manuscript, we compiled these results with some concluding remarks. We found physical environmental changes of water cycle, sea-ice and ocean conditions, heat transport, and ocean mixing in the Arctic Ocean and surrounding areas. We also examined chemical properties, carbon, cycle, and ocean acidification in the Arctic Ocean. In addition, new findings regarding impacts of sea-ice reduction to primary productivities were published. For public outreach of Arctic research, we were able to develop an educational tool (a board game named “The Arctic”) in collaboration with Themes 6 and 7. journal article